2015
DOI: 10.1515/igbp-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Monsoonal Droughts In India – A Recent Assessment

Abstract: Drought frequencies during the years 1901–2010 were investigated over three spatial units – All India, 5 Homogeneous Regions (HR) and 36 Meteorological subdivisions (MSs). The All-India rainfall trend is in fact indicative of no trend, while the Northeast HR (NER) shows a significant decrease. Furthermore, a significant decrease in rainfallis to be observed over Himachal Pradesh, Madhya Pradesh, Maharashtra and the Southern Peninsular region, and a significant increase over West Bengal, Punjab, Haryana, Coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Further considering other time scales, the most prominent years were 1905, 1918, 1964, 1965, 1972, 1987, 2001, and at a 12-month scale. These extreme droughts have been reported in various literature mentioning the potential impact over diverse fields such as agriculture, water reservoir (Tyalagadi et al 2015;Samra 2004;Parthasarthy et al 1987Parthasarthy et al , 1994Shewale & Kumar 2005). It is well documented that 70% of the Indian region has suffered from the occurrence of extreme drought in 1918, which was designed as first large drought in India followed by second-largest drought in 1987 and 1905, which affected 48% and 37% of the area, respectively (Shewale & Kumar 2005).…”
Section: Severity Assessment Of Extreme Drought and Wet Yearsmentioning
confidence: 86%
“…Further considering other time scales, the most prominent years were 1905, 1918, 1964, 1965, 1972, 1987, 2001, and at a 12-month scale. These extreme droughts have been reported in various literature mentioning the potential impact over diverse fields such as agriculture, water reservoir (Tyalagadi et al 2015;Samra 2004;Parthasarthy et al 1987Parthasarthy et al , 1994Shewale & Kumar 2005). It is well documented that 70% of the Indian region has suffered from the occurrence of extreme drought in 1918, which was designed as first large drought in India followed by second-largest drought in 1987 and 1905, which affected 48% and 37% of the area, respectively (Shewale & Kumar 2005).…”
Section: Severity Assessment Of Extreme Drought and Wet Yearsmentioning
confidence: 86%
“…The ENSO is one of the significant climate variables influenced by rainfall over the South Asian region. El Niño has been linked to 13 out of 21 droughts observed in India during the last century [138]. Rahman et al [139] analyzed SPI-3 and revealed that moderate and extreme droughts are associated with El-Nino events.…”
Section: Drought Prediction Teleconnection and Projection Under Climate Changementioning
confidence: 99%
“…The most severe droughts in the past have affected more than 60% of the area of the entire country (De, Dube and Rao, 2005). Overall, the frequency of droughts in India is estimated to be between 1 in every 4 and 1 in every 5 years (Pandey and Bhandari, 2009;Tyalagadi, Gadgil and Krishnakumar, 2015;Saini and Gulati, 2014;Mall et al, 2006).…”
Section: Policy Performance In the Face Of Riskmentioning
confidence: 99%